Physical, mechanical and neutron shielding properties of h-BN/Gd2O3/HDPE ternary nanocomposites - Irim, S. Gozde; Wis, Abdulmounem Alchekh; Keskin, M. Aker; Baykara, Oktay; Ozkoc, Guralp; Avci, Ahmet; Karakoc, Mesut (Pergamon-Elsevier Science Ltd, 2018)
In order to prepare an effective neutron shielding material, not only neutron but also gamma absorption must be taken into account. In this research, a polymer nanocomposite based novel type of multifunctional neutron shielding material is designed and fabricated. For this purpose, high density polyethylene (HDPE) was compounded with different amounts of hexagonal boron nitride (h-BN) and Gd2O3 nanoparticles having average particle size of 100 nm using melt-compounding technique. The mechanical, thermal and morphological properties of nanocomposites were investigated. As filler content increased, the absorption of both neutron and gamma fluxes increased despite fluctuating neutron absorption curves. Adding h-BN and Gd2O3 nano particles had a significant influence on both neutron and gamma attenuation properties (Sigma, cm(-1) and mu/rho cm(-2)/g) of ternary shields and they show an enhancement of 200-280%, 14-52% for neutron and gamma radiations, respectively, in shielding performance.
Keywords: Neutron; Gamma; Boron nitride; Gadolinium oxide; Nano-particles; Nanocomposites